Mission And Evangelism: African Context - Halim Wiryadinata (KURIOS (Jurnal Teologi dan Pendidikan Agama Kristen), 2015)
This essay is a critical assessment of the shift in message and meaning of mission since the Edinburgh 1910 Conference. The essay will also include a clarification of the Lausanne documents on mission discussed by John Stott. Against the background of this critical assessment, I will suggest what should be the content and expression of the Gospel as it would be presented in an African context as discussed by David Gitari and Byang Kato. But before I discuss the above I will highlight the tension in mission.